THE ROLE OF THE PRESIDENCY IN THE FUNCTIONING OF THE EUROPEAN UNION ROMANIAN PRESIDENCY OF THE EU COUNCIL - CHALLENGES AND OPPORTUNITIES - Dragoș – Adrian BANTAȘ (Challenges of the Knowledge Society, 2019)
This year, for the first time in the history of its membership in the European Union, Romania exercises the rotating presidency of the Council of the European Union. As far as the Council is concerned, it is undoubtedly one of the most important decision-making factors, part of what the specialized doctrine calls the "bicameral legislative of the European Union". The manner of exercising the presidency, the role of the Presidency in the proper functioning of the Council, the challenges and opportunities related to it are, in our opinion, topics of interest for the Romanian public and their approach can bring more clarity to the debates held in this honorable, but the difficult period. That's exactly why the aforementioned subjects are the research topic of the research paper that we submit to your attention in the lines below.